2009
DOI: 10.1016/j.ejcts.2008.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Does pretransplant left ventricular assist device therapy improve results after heart transplantation in patients with elevated pulmonary vascular resistance?

Abstract: Pretransplant LVAD therapy reduces an elevated PVR in heart transplant recipients, but there was no statistically significant difference in posttransplant survival in patients with PH with, or without LVAD therapy. The study revealed no differences in survival in patients regardless of the severity of the PH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 15 publications
1
50
0
Order By: Relevance
“…The aim of treatment of secondary PH is to normalize the wedge pressure, and, consequently, LVAD support can play a crucial role. Since the beginning of the 1990s, many authors have shown a decrease of PH during LVAD support [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Table 5 shows an overview of all literature data and results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The aim of treatment of secondary PH is to normalize the wedge pressure, and, consequently, LVAD support can play a crucial role. Since the beginning of the 1990s, many authors have shown a decrease of PH during LVAD support [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Table 5 shows an overview of all literature data and results.…”
Section: Discussionmentioning
confidence: 98%
“…Some authors, such as Martin et al [13], Etz et al [11] and Zimpfer et al [18], considered only patients who did not respond to drugs, and others, such as Smedira et al [17] and Liden et al [12], gave a cutoff in terms of pulmonary hemodynamic parameters values to define a clinical scenario of severe PH. Consequently, we decided to divide our patient population into two different groups: responders and non-responders to inotrope therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A widely used salvage strategy for acute graft failure is temporary mechanical circulatory support using venoarterial extracorporeal membrane oxygenation or short-term left or right ventricular assist devices as a bridge to recovery or RTx (8). Recent publications have been encouraging by demonstrating that long-term outcomes for HTx recipients with preoperative left ventricular assist devices were comparable to those without (29)(30)(31). Careful patient selection and perioperative care is paramount considering the limited allograft resources.…”
Section: Discussionmentioning
confidence: 99%
“…Left ventricular assist devices (LVADs) have been widely adopted by most transplantation programs to stabilize decompensated heart failure patients awaiting primary transplantation; recent publications have suggested that long-term outcomes for patients with preoperative LVADs were comparable to results for those without. [15][16][17] Patients in our series had intra-aortic balloon pumps and extracorporeal membrane oxygenation available, but no other LVADs or mechanical assist devices were used until recently.…”
Section: Discussionmentioning
confidence: 99%